Effect of Carbon Nanoparticles (CNPs) as an Additive on the Performance of Food-grade Lubricant Grease Formulation - Syubaikah Badrul; Siti Maisurah Maudoode; Mohd Zuhan, Mohd Khairul Nizam; Najmuddin Mohd Ramli; Mohd Najib Razali (Multidisciplinary Applied Research and Innovation, 2024)
This study aimed to formulate food-grade lubricating grease using vegetable oil as base oil, aluminium isopropoxide blended with hydroxystearic acid as a thickener, and graphene (carbon nanoparticles) as an additive. This research also aims to analyse the effect of graphene as an additive in different formulations using different characterisation methods. The grease analysis studied was the penetration test (ASTM D-217) and the drop point test (ASTM D-2265). Three formulations were made in the study consisting of formulation 1 (F1), formulation 2 (F2) and formulation 3 (F3) with 0 %, 1 % and 2 % of additive added into the formulation, respectively. The results show that the F1 consistency of the grease is in the range of the grease formulated. Graphene significantly contributed to the performance of food-grade grease formulations with higher mechanical stability, but the dropping point was lower than expected. This formulation grease might improve based on another method consisting of other components or materials.